Fluid paths to the cabinet in federal presidential systems: Argentina 1983–2020 - Camerlo, Marcelo (2022)
The study of political careers has focused mainly on highly institutionalized systems. This article examines the extent to which the findings from this research agenda apply to more fluid settings, looking at trajectories to the national cabinet in a regime combining presidentialism and federalism: Argentina from 1983 to 2020. We propose an operationalization of political career that integrates five definitional dimensions, looks at full sequences of single occupational positions, and tests six expectations derived from the literature. When only political jobs are taken into account, we found that careers show significant movement from the subnational level and predominance of executive experience. However, when all occupational jobs are considered, political positions are pulled into second place behind the private sector. Most unexpectedly, in a significant percentage of cases, a ministerial position does not appear to be the last step of a political career but rather an initial springboard thereof.